Days to re-entrainment following the spring and autumn changes in local clock time: beyond simple heuristics - Rea, Mark S.; Nagare, Rohan; Bullough, John D.; Figueiro, Mariana G. (Frontiers in Photonics, 2024)
Circadian disruption, a breakdown in the regularity of activity patterns across the 24-h day, can lead to a variety of maladies. Some individuals and organizations object to the twice-yearly, seasonal changes in local time because it contributes to circadian disruption. The number of days required to re-entrain the circadian system to the new local time following transitions to or from daylight saving time is not completely understood, but several simple rules of thumb (i.e., heuristics) have been offered to minimize the days to re-entrainment and, thus, circadian disruption (e.g., go for a morning walk). Recently, the authors developed a computational model for predicting circadian phase from calibrated light-dark exposure patterns, based largely on the pioneering work of Kronauer and colleagues. This model was used here to predict the days to re-entrainment of the circadian systems of “larks” and “owls” to a new local time if they were exposed to one of three specific light interventions. Simulations showed that the timing of a light intervention must account for chronotypes (e.g., timing of minimum core body temperature) and direction of shift (i.e., phase advance or delay) to achieve re-entrainment to the time change more quickly. Simple heuristics are not necessarily adequate for minimizing the days to re-entrainment.